Sex and Race Differences in Lifetime Risk of Heart Failure With Preserved Ejection Fraction and Heart Failure With Reduced Ejection Fraction. Issue 17 (24th April 2018) - Pandey, Ambarish; Omar, Wally; Ayers, Colby; LaMonte, Michael; Klein, Liviu; Allen, Norrina B.; Kuller, Lewis H.; Greenland, Philip; Eaton, Charles B.; Gottdiener, John S.; Lloyd-Jones, Donald M.; Berry, Jarett D.
Abstract : Background: Lifetime risk of heart failure has been estimated to range from 20% to 46% in diverse sex and race groups. However, lifetime risk estimates for the 2 HF phenotypes, HF with preserved ejection fraction (HFpEF) and HF with reduced ejection fraction (HFrEF), are not known. Methods: Participant-level data from 2 large prospective cohort studies, the CHS (Cardiovascular Health Study) and MESA (Multiethnic Study of Atherosclerosis), were pooled, excluding individuals with prevalent HF at baseline. Remaining lifetime risk estimates for HFpEF (EF ≥45%) and HFrEF (EF <45%) were determined at different index ages with the use of a modified Kaplan-Meier method with mortality and the other HF subtype as competing risks. Results: We included 12 417 participants >45 years of age (22.2% blacks, 44.8% men) who were followed up for median duration of 11.6 years with 2178 overall incident HF events with 561 HFrEF events and 726 HFpEF events. At the index age of 45 years, the lifetime risk for any HF through 90 years of age was higher in men than women (27.4% versus 23.8%). Among HF subtypes, the lifetime risk for HFrEF was higher in men than women (10.6% versus 5.8%). In contrast, the lifetime risk for HFpEF was similar in men and women. In race-stratified analyses, lifetime risk for overall HF was higher in nonblacks than blacks (25.9% versus 22.4%). Among HF subtypes, the lifetime risk for HFpEF was higher in nonblacks than blacks (11.2% versus 7.7%), whereas that for HFrEF was similar across the 2 groups. Among participants with antecedent myocardial infarction before HF diagnosis, the remaining lifetime risks for HFpEF and HFrEF were up to 2.5-fold and 4-fold higher, respectively, compared with those without antecedent myocardial infarction. Conclusions: Lifetime risks for HFpEF and HFrEF vary by sex, race, and history of antecedent myocardial infarction. These insights into the distribution of HF risk and its subtypes could inform the development of targeted strategies to improve population-level HF prevention and control. Abstract : Supplemental Digital Content is available in the text.